Excellent electrocatalytic effects of tin through in situ electrodeposition on the performance of all-vanadium redox flow batteries - Mehboob, Sheeraz; Mehmood, Asad; Lee, Ju-Young; Shin, Hyun-Jin; Hwang, Jinyeon; Abbas, Saleem; Ha, Heung Yong (ROYAL SOC CHEMISTRY, 2017)
This work unfolds novel electrocatalytic effects of tin for all-vanadium redox flow batteries (VRFBs). By the introduction of Sn2+ ions into the electrolyte, tin nanoparticles are in situ electrodeposited on a carbon felt electrode. The effectiveness of the two tin species (Sn2+ and Sn4+) as well as their impact on the kinetics of cathode (VO22+/VO2+) and anode (V3+/V2+) half-reactions are also evaluated comprehensively. Cyclic voltammetry reflects the excellent improvement in reaction kinetics, particularly for the anode half-reaction (i.e. V3+/V2+ reduction) by reducing its peak potential separation from 1011 to 589 mV, owing to the deposition of tin nanoparticles in its vicinity. The electrocatalytic effects of tin cause a significant improvement in key performance parameters of voltage efficiency, energy efficiency (EE), specific discharge capacity, discharge energy density and cycling stability for VRFBs. The VRFBs employing Sn2+ ions in the anolyte exhibit an EE of 77.3% at a high current density of 150 mA cm(-2) while the corresponding specific discharge capacity and discharge energy density are increased by 26.2 and 32.0%, respectively, as compared to the pristine system. Thus, electrolyte utilization is also increased at faster charge/discharge rates due to the reduction of overpotentials. Various characterization techniques confirm the deposition and effectiveness of tin at the electrodes. EIS studies reveal remarkable acceleration in the charge transfer process for the V3+/V2+ redox couple which is considered as a performance limiting reaction for VRFBs nowadays. Therefore, the convenience in its application coupled with effectiveness for VRFBs, makes tin a commercially feasible electrocatalyst for this technology.
Keywords: CARBON FELT ELECTRODE; GRAPHITE FELT; ELECTROCHEMICAL PERFORMANCE; POSITIVE ELECTRODE; FUNCTIONAL-GROUPS; ENERGY-STORAGE; GLASSY-CARBON; COMPOSITE; PRETREATMENT; DEGRADATION